Assessing Food Security Scenario at the Ward Level in Nepal: An Analysis of Caloric Needs from Diverse Crops Based on Location-Specific Factors and Policy Implications - Bhattarai, Keshav; Gautam, Shiva Prasad; Gyawali, Buddhi Raj (Nepal Public Policy Review, 2023)
Food security means access to food along with food production and availability to every individual at a reasonable cost according to the calorific needs of people. To assure food safety to 30 million Nepali people, it is essential to utilize every piece of available farmable land in each geographic region of seven provinces. We analyzed individual household food intake, dietary energy adequacy, and nutritional status and needs at the ward level of Nepal. We used a decadal (2010-2020) average food production of different crops per unit of farmable area, and food needs for people living in that ward based on their gender and nutritional requirements to perform various activities in different geographic regions of seven provinces. We assumed three food consumption scenarios: a) traditional practices of meeting dietary needs only from major crops; b) consuming major and minor crops; and c) consuming major and minor crops and meat and fruit products. Our analysis revealed that it is essential for Nepal to implement policies that will encourage crop diversification comprising both major and minor crops and inform the public about the nutritional values of various crops that can be grown utilizing location-specific environments in different geographic regions of seven provinces. Our findings assist in policy instrumentation that will pursue farming communities to supplement their dietary needs with diverse crop products and suggest government set aside some matching funds to encourage remitters, who return to Nepal with knowledge and financial resources, to engage in agriculture. We also argue that crop diversification is needed to assure farm productivity if certain crops fail due to unforeseen environmental calamities.